2009
DOI: 10.1007/978-1-84882-599-4_12
|View full text |Cite
|
Sign up to set email alerts
|

HoCaMA: Home Care Hybrid Multiagent Architecture

Abstract: Home Care is one of the main objectives of Ambient Intelligence. Nowadays, the disabled and elderly population, which represents a significant part of our society, requires novel solutions for providing home care in an effective way. In this chapter we present HoCaMA, a hybrid multiagent architecture that facilitates remote monitoring and care services for disabled patients at their homes. HoCaMA combines multiagent systems and Web services to facilitate the communication and integration with multiple health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Although several promising prototypes have been done in academia [11,13,1,5], yet there are many challenges and hurdles to overcome before having a realistic homecare solution [12,9]. Based on our study, we observed that existing solutions have not addressed dynamic provisioning and its requirements as much as other challenges such as distributed and heterogeneous application service providers [23].…”
Section: Introductionmentioning
confidence: 88%
“…Although several promising prototypes have been done in academia [11,13,1,5], yet there are many challenges and hurdles to overcome before having a realistic homecare solution [12,9]. Based on our study, we observed that existing solutions have not addressed dynamic provisioning and its requirements as much as other challenges such as distributed and heterogeneous application service providers [23].…”
Section: Introductionmentioning
confidence: 88%
“…Agent technology has been appointed as a proper technology for the support of AmI solutions [4,10,31]. In fact, agents show interesting characteristics for AmI environments since they are reactive, proactive and social [36].…”
Section: Introductionmentioning
confidence: 99%
“…Agent technology has been appointed as a proper technology for the support of AmI solutions (22,47,48 reducing the use of memory (also related with the number of offers sampled). Additionally, economic requirements (e.g., utility of the final agreement) should not be forgotten.…”
Section: Automated Negotiation and Ambient Intelligencementioning
confidence: 99%